Journal of Hospitality & Tourism Research. (Teller Road, Thousand Oaks, California : SAGE Publication, 2023)
b
u
u
u
u
b
u
u
u
u
Effects of Perceived Placeness on Tourists' Authenticity Experience Via the Mediating Role of Flow Experience -- Tourist Inspiration: How the Wellness Tourism Experience Inspires Tourist Engagement -- Booth Attractiveness: Scale Development and Model Testing from a Mental Budgeting Perspective -- Proposing a Cyclic Model of Tourist Decision Making: A Review and Integration of Behavioral and Choice-Set Models -- What's Wrong with Different Empowerment? The Effect of Differentiated Empowering Leadership on Employee Proactive Service -- The Effect of Waiters' Occupational Identity on Employee Turnover Within The Context of Michelin-Starred Restaurants -- The Effects of Unfulfilled Preferential Treatment and Review Dispersion on Airbnb Guests' Attitudes and Behavior -- Transforming Brand Identity to Hotel Performance: The Moderating Effect of Social Capital -- Effects of Abnormal Weather Conditions on the Performance of Hotel Firms -- The Copycat Effect: Do Hotel-Like Features Drive Airbnb Performance?.
Includes bibliographical references.